Creating and deploying solutions with IBM Integrated Runtime V1.1 - Bick, Shih-in (IBM redbooks., 2004)
Small and medium-sized businesses are among the fastest-growing segments of the global economy. As these businesses strive to capture opportunities in a rapidly changing marketplace, they often turn to independent software vendors (ISVs) for the IT solutions they need. Large enterprises also require customized solutions to help them stay competitive in the global marketplace. This IBM Redbooks publication describes how ISVs and corporate information technology centers can use IBM Integrated Runtime V1.1 to deploy solutions to their customers quickly and efficiently. By reducing the complexity of deploying complete solutions, Integrated Runtime shortens time-to-market for ISVs and reduces time-to-productivity for users. The result is efficient deployment of solutions by ISVs and corporate technology departments, rapid access to new solutions by users, and improved customer satisfaction. This book is intended for: - ISVs and Information Technology departments who are evaluating Integrated Runtime - New users of Integrated Runtime - IBM client teams who want to demonstrate the benefits of Integrated Runtime to potential users - IBM teams and others who are responsible for supporting Integrated Runtime users Please note that the additional material referenced in the text is not available from IBM.